The Impact Of The Explicit Integration Of Islam In Counseling: Implications For Interpersonal Relationship Development Theory - Priester, Paul E. (Research in the social scientific study of religion, 2009)
This study examined the impact of the inclusion of Islam in counseling, on the perceptions of a sample of Jordanian college students (n = 290). This article employed an analogue format that compared three counselor descriptions: one that explicitly included religion in counseling; one that explicitly did not include religion in counseling; and a control condition in which no statement about religion was made. Planned comparisons found that the participants viewed the clinician who explicitly did not include religion as being less socially attractive and less trustworthy. These results offer support for Rosenbaum’s Repulsion Hypothesis within the theoretical framework of Interpersonal Relationship Development.